Robust monetary policy in a small open economy - Kai Leitemo; Ulf Söderström (Bank of Finland, 2005)
This paper studies how a central bank's preference for robustness against model misspecification affects the design of monetary policy in a New-Keynesian model of a small open economy.Due to the simple model structure, we are able to solve analytically for the optimal robust policy rule, and we separately analyse the effects of robustness against misspecification concerning the determination of inflation, output and the exchange rate.We show that an increased central bank preference for robustness makes monetary policy respond more aggressively or more cautiously to shocks, depending on the type of shock and the source of misspecification.
URN:NBN:fi:bof-20140807575
Keywords: E52; E58; F41; 330; Knightian uncertainty; min-max policies; model uncertainty and robust control